Survey parameters for detecting 21-cm-Ly a emitter cross-correlations with the Square Kilometre Array - Hutter, A.; Trott, Cathryn; Dayal, P. (Wiley-Blackwell Publishing Ltd., 2018)
Detections of the cross-correlation signal between the 21 cm signal during reionization and high-redshift Lyman-a(Ly a) emitters (LAEs) are subject to observational uncertainties which mainly include systematics associated with radio interferometers and LAE selection. These uncertainties can be reduced by increasing the survey volume and/or the survey luminosity limit, i.e. the faintest detectable Ly a luminosity. We use our model of high-redshift LAEs and the underlying reionization state to compute the uncertainties of the 21-cm-LAE crosscorrelation function at z ?6.6 for observations with SKA1-Low and LAE surveys with ?z =0.1 for three different values of the average inter-galactic medium (IGM) ionization state (<?HI>? 0.1, 0.25, 0.5). At z?6.6, we find SILVERRUSH type surveys, with a field of view of 21 deg2and survey luminosity limits of La=7.9×1042erg s-1, to be optimal to distinguish between an IGM that is 50, 25, and 10 per cent neutral, while surveys with smaller fields of view and lower survey luminosity limits, such as the 5 and 10 deg2surveys with WFIRST, can only discriminate between a 50 and 10 per cent neutral IGM.